Food Safety: Five Steps to Food Safety - Jennifer Hillan (EDIS)
Revised! FCS8634, a one-page fact sheet by Jennifer Hillan, lists the five key steps consumers should take to ensure food safety. Published by the UF Department of Family, Youth and Community Sciences, August 2006.